Hygiene in food processing : principles and practice - Lelieveld, H. L. M.; Holah, J. T.; Napper, D. (Woodhead Publishing in food science, technology, and nutrition ;, 2014)
The hygienic processing of food concerns both the potential hazards in the food products and the regulation, design and management of food processing facilities. This second edition of Hygiene in food processing gives a revised overview of the practices for safe processing and incorporates additional chapters concerning pest control, microbiological environmental sampling and the economics of food plants. Part one addresses the risks of microbial foods and the corresponding regulation in the EU. Part two discusses the hygienic design of food factory infrastructure, encompassing the desi.